Hoya phuwuaensis (Apocynaceae: Asclepiadoideae), a new species from Northeastern Thailand - Kidyoo, Manit (Phytotaxa, 2016)
The new species, Hoya phuwuaensis is described and illustrated. It was discovered in Phu Wua Wildlife Sanctuary, Bueng Kan Province, northeastern Thailand. Hoya phuwuaensis is similar to the widespread and common species H. caudata. Both species have prominent mottling of silver spots on the adaxial leaf surface and positively geotropic inflorescences with slender peduncles. However, the new species can be distinguished from H. caudata by its elliptic leaf with cuneate base, obovate-oblong corona lobe and triangular anther appendages.Brown, R. (1810) Prodromus Florae Novae Hollandiae et Insulae Van-Diemen, etc. Leornard Schrag, Nuremberg.Decaisne, J. (1844) Asclepiadaceae. In: Candolle, A.P. de (Ed.) Prodromus Systematis Naturalis Regni Vegetabilis 8. Fortin, Masson & Sociorum, Paris, pp. 490–665.Hooker, J.D. (1883) The Flora of British India 4. Reeve & Co., London, 780 pp.Kerr, A.F.G. (1940) Hoya flagellata Kerr. Hooker’s Icones Plantarum 35: t. 3407.IUCN Standards and Petitions Subcommittee (2016) Guidelines for using the IUCN Red List categories and criteria. Version 12. Prepared by the Standards and Petitions Subcommittee. Available from: http://www.iucnredlist.org/documents/RedListGuidelines.pdf (accessed 13 September 2016)Kerr, A.F.G. (1951) Hoya R.Br. In: Pendleton, R.L. (Ed.) Florae Siamensis Enumeratio 3 (1). Siam Society, Bangkok, pp. 35–42. Kidyoo, M. (2013) Hoya soidaoensis kidyoo, a new species of Hoya (Asclepiadaceae) from Eastern Thailand. Phytotaxa 105 (2): 45–50.         http://dx.doi.org/10.11646/phytotaxa.105.2.3Kidyoo, M. (2015) Hoya rostellata (Apocynaceae: Asclepiadoideae), a new species from Thailand. Taiwania 60 (1): 39–42.Li, P.T, Gilbert, M.G. & Stevens, W.D. (1995) Asclepiadaceae. In: Wu, Z.Y. & Raven, P.H. (Eds.) Flora of China. 16. Science Press, Beijing & Missouri Botanical Garden, St. Louis, pp.189–270.Ridley, H.N. (1923) Hoya Br. In: Ridley, H.N. (Ed.) The Flora of the Malay Peninsula 2. Reeve & Co., London, pp. 393–402.Rintz, R.E. (1978) The Peninsular Malaysian species of Hoya (Asclepiadaceae). Malaysian Nature Journal 30: 467–522.Rodda, M. & Simonsson Juhonewe, N. (2011) Hoya mappigera (Apocynaceae, Asclepiadoideae), a new campanulate flowered species from Peninsular Malaysia and southern Thailand. Feddes Repertorium 122: 1–7.         http://dx.doi.org/10.1002/fedr.201100019Rodda, M. & Ang, W.F. (2012) Hoya caudata Hook.f. (Apocynaceae), A new record for Singapore, and keys to the Hoya species of Singapore. Nature in Singapore 5: 123–128.Schlechter R. (1916) Neue Asclepiadaceen von Sumatra und Celebes. Beihefte zum Botanischen Centralblatt 34: 1–18.Thaithong, O. (1995) The genus Hoya in Thailand. In: Kiew, R. (Ed.) The Taxonomy and Phytochemistry of the Asclepiadaceae in Tropical Asia. University Pertanian, Malaysia, pp. 83–94.Wanntorp, L., Kocyan, A., van Donkelaar, R. & Renner, S.S. (2006) Towards a monophyletic Hoya (Marsdenieae, Apocynaceae): Inferences from the chloroplast trnL region and the rbcL-atpB spacer. Systematic Botany 31: 586–596.             http://dx.doi.org/10.1600/036364406778388593